Gambaran Perubahan Tekanan Darah Pada Pasien Gagal Ginjal Kronik Yang Menjalani Terapi Hemodialisis Di Ruang Hemodialisa Rumah Sakit TK. II Pelamonia Makassar - Abdul Herman Syah Thalib ((JKG) Jurnal Keperawatan Global, 2019)
Background: The kidneys have a very important role in maintaining a healthy body. The kidneys experience acute renal failure when the kidney cannot function suddenly. Without kidney replacement therapy, deaths from metabolic disorders can occur quickly. One kidney replacement therapy can be done is hemodialysis. Although hemodialysis is safe and beneficial for patients, it does not mean without side effects. Various complications can occur when patients undergo hemodialysis one of which is intradialisis hypertension. This complication can lead to new, more complex problems, including discomfort, increasing stress affecting the quality of life, worsening the patient's condition and even causing death. Objective To determine the description of blood pressure changes in patients with chronic renal failure undergoing hemodialysis therapy in the Hemodialysis room at TK II Pelamonia Hospital Makassar. Methods: This study used a descriptive survey method with a case study approach. Results: Research shows that patients undergoing hemodialysis therapy experience changes in blood pressure in pre and post hemodialysis. Conclusion: There is an effect of hemodialysis on changes in blood pressure in patients with kidney failure in the Hemodialysis Room of TK. II Pelamonia Hospital Makassar.